STUDENTS’ PERCEPTIONS OF MOTIVATIONAL TEACHING STRATEGIES IN ENGLISH AS FOREIGN LANGUAGE (EFL) CLASSROOM - Wirentake, Wirentake (Jurnal TAMBORA, 2017)
This study was aimed at investigating students’ perception of motivational teaching strategies in English as Foreign Language (EFL) classroom, specifically on what motivational teaching strategies do students consider important and what are their reasons of considering the strategies as important. This study was a descriptive qualitative study. The instruments employed were questionnaire and interview. Based on the findings, the motivational teaching strategies considered most important are: (1) establish good relationship with students; (2) teachers should bring humors into the classroom; (3) teachers should show their enthusiasm for teaching; (4) teachers should show students that they care about them; (5) teachers should give clear instruction about how to carry a task; (6) teachers should make sure that grades reflect students achievement and effort; (7) teachers should invite English-speaking foreigners to class; (8) teachers should use a short and interesting opening activity to start each class; (9) teachers should avoid social comparison and (10) teachers should be themselves in front of students. In addition, one of the common reasons of why students considered those motivational teaching strategies as important was because they believed that those strategies are able to boost their motivation in learning English if it is implemented by their teachers.